2021 IEEE International Memory Workshop (IMW) 2021
DOI: 10.1109/imw51353.2021.9439590
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer OTS Selectors Engineering for High Temperature Stability, Scalability and High Endurance

Abstract: We present the engineering of Ovonic Threshold Switching (OTS) Multilayer (ML) Selector device based on the stacking of N-doped SbSe and Ge layers. By tuning individual layers thicknesses and N content of the ML stack, we demonstrate the possibility to highly improve selector stability during integration Back-End-of-Line (BEOL) and to reduce device-to-device variability. We show how our OTS ML presents fundamental electrical characteristics that are compatible with the ones of standard bulk OTS achieved by co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…SAGS spectrum shows an evolution after annealing, which could correspond to the starting of material segregation. As shown in our previous work on SbSe-based OTS [6], the ML structure delays structural changes related to crystallization process in OTS layers. Indeed, the introduction of GeN layers in SAGS increases the Ge-Se bonds with respect to As-Se and Si-Se because of interlayer interactions leading and Ge-Se features around 190 cm 1 (and 212 cm 1 for ML) [8,11]- [13] with Ge-Ge shoulders at 300 cm 1 .…”
Section: Ots Physico-chemical Analysesmentioning
confidence: 52%
See 2 more Smart Citations
“…SAGS spectrum shows an evolution after annealing, which could correspond to the starting of material segregation. As shown in our previous work on SbSe-based OTS [6], the ML structure delays structural changes related to crystallization process in OTS layers. Indeed, the introduction of GeN layers in SAGS increases the Ge-Se bonds with respect to As-Se and Si-Se because of interlayer interactions leading and Ge-Se features around 190 cm 1 (and 212 cm 1 for ML) [8,11]- [13] with Ge-Ge shoulders at 300 cm 1 .…”
Section: Ots Physico-chemical Analysesmentioning
confidence: 52%
“…4. SAGS devices do not show functionality above 250 • C. At the same time, the leakage current (I off ) increases with operating temperature as already observed in [4,6]. The saturation voltage E m for each voltage is obtained by current vs temperature fitting (not reported) compatibly with [17] for virgin (before firing) and initialized devices (after firing).…”
Section: A High Operating Temperature Effectsmentioning
confidence: 65%
See 1 more Smart Citation
“…[26] Lagnua et al suggested a specific multi-layered chalcogenide structure for a thermally stable OTS device. [27] The thermal stability of OTS materials can also benefit the endurance characteristics of OTS because the stability of the localized electronic traps in the amorphous chalcogenides is the most influential factor in the operation voltage distribution of an OTS and its low leakage current level. In addition, to ensure high endurance characteristics, the current overshoot (the so-called "surge current") should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that the heterostructures of different chalcogenide can be tried to improve the performance of OTS devices, referring to the phase change heterojunction of phase change devices [19−21] . Furthermore, some reported multilayer OTS selectors were recently put forward with too much layers, which make it difficult to manufacture [21,22] . Therefore, a novel structure with simple multilayer is a new idea of device optimization and is quite necessary to be proposed.…”
Section: Introductionmentioning
confidence: 99%